2021
DOI: 10.1186/s12886-021-01988-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of retinal vessel density and thickness changes in diabetes mellitus evaluated using optical coherence tomography angiography: a cross-sectional study

Abstract: Background Diabetic retinopathy is the most common microvascular complication of diabetes; however, early changes in retinal microvessels are difficult to detect clinically, and a patient’s vision may have begun to deteriorate by the time a problem is identified. Optical coherence tomography angiography (OCTA) is an innovative tool for observing capillaries in vivo. The aim of this study was to analyze retinal vessel density and thickness changes in patients with diabetes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…Similarly, the duration of DM disease is also a risk factor for the development of DR, and the longer the duration of DM disease is, the greater the risk of nerve fiber and vascular damage in the retina. This finding is consistent with some previous studies [ 22 ]. Our updated study showed a negative correlation between the thickness of the inferior and center subdivisions of the GCL and the duration of DM disease, suggesting that RGCs are damaged as the duration of DM disease increases.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, the duration of DM disease is also a risk factor for the development of DR, and the longer the duration of DM disease is, the greater the risk of nerve fiber and vascular damage in the retina. This finding is consistent with some previous studies [ 22 ]. Our updated study showed a negative correlation between the thickness of the inferior and center subdivisions of the GCL and the duration of DM disease, suggesting that RGCs are damaged as the duration of DM disease increases.…”
Section: Discussionsupporting
confidence: 94%
“…Temporal RNFL thickness was positively correlated with the vessel density of the superficial retinal vascular layer. [ 16 ] In the present study, we have taken average RNFL thickness and average vessel density as well as superior and temporal quadrant RNFL thickness and vessel density specifically and found comparable results to the aforesaid findings of earlier studies.…”
Section: Discussionsupporting
confidence: 89%
“…Studies on normal subjects or diabetic patients using OCT-A support that it is characterized by satisfactory repeatability and sensitivity and could detect retinal vascular diseases at an early stage. [24][25][26][27][28] Recently, efforts to register images of a specified retinal area resulting from FA and OCT-A have been recorded. It was concluded that these imaging modalities complement each other successfully regarding imaging and interpretation of vascular diseases, as success rate was 98.8% and best mean execution time was less than 5 sec per image.…”
Section: Discussionmentioning
confidence: 99%